Antibiosis and Tolerance to Five Species of Spittlebug (Homoptera: Cercopidae) in Brachiaria spp.: Implications for Breeding for Resistance - Cardona, César; Fory Sánchez, Paola Andrea; Sotelo, Guillermo; Pabón, Alejandro; Díaz, Giovanna; Miles, John W. (Oxford University Press, 2004)
Several genera and species of spittlebugs (Homoptera: Cercopidae) are economic pests of Brachiaria spp. grasses in tropical America. To support current breeding programs aimed at obtaining multiple spittlebug resistance, we undertook a series of studies on antibiosis and tolerance as possible mechanisms of resistance to five major spittlebug species affecting Brachiaria spp. in Colombia: Aeneolamia varia (F.), Aeneolamia reducta (Lallemand), Zulia carbonaria (Lallemand), Zulia pubescens (F.), and Mahanarva trifissa (Jacobi). Four host genotypes, well known for their reaction to A. varia attack, were used to compare their resistance to other spittlebug species: CIAT 0654 and CIAT 0606 (susceptible) and CIAT 6294 and CIAT 36062 (resistant). CIAT 0654 and CIAT 36062 were used in antibiosis studies. Tolerance studies were conducted with CIAT 0654, CIAT 6294, and CIAT 36062. Sixty-five hybrid-derived clones were used to identify levels of multiple resistance to three spittlebug species. The levels of antibiosis resistance in CIAT 36062 clearly differed by spittlebug species and were classified as follows: very high for M. trifissa, high for A. varia and A. reducta, moderate for Z. pubescens, and absent for Z. carbonaria. Our results suggest the presence of true tolerance to Z. carbonaria in CIAT 6294 and CIAT 36062, true tolerance to Z. pubescens in CIAT 6294 and a combination of tolerance and antibiosis as mechanisms of resistance to Z. pubescens in CIAT 36062. Of the 65 hybrid clones tested with A. varia, A. reducta, and Z. carbonaria, 15 combined resistance to two species and three showed antibiosis resistance to all three spittlebug species.